A Correlation-Based Feature Selection Algorithm for Operating Data of Nuclear Power Plants. (29th August 2021) - He, Yuxuan; Yu, Hongxing; Yu, Ren; Song, Jian; Lian, Haibo; He, Jiangyang; Yuan, Jiangtao
Abstract : Nuclear power plant operating data are characterized by a large variety, strong coupling, and low data value density. When using machine learning techniques for fault diagnosis and other related research, feature selection enables dimensionality reduction while maintaining the physical meaning of the original features, thus improving the computational efficiency and generalization ability of the learning model. In this paper, a correlation-based feature selection algorithm is developed to implement feature selection of nuclear power plant operating data. The proposed algorithm is verified by experiments and compared with traditional correlation-based feature selection algorithms. The experiments and comparison results show that the proposed algorithm is effective in realizing the dimensionality reduction of nuclear power plant operating data.